Структурная идентификация интервальных моделей статических систем - Дывак, Н.П.; Манжула, В.И. (Проблемы управления и информатики, 2008)
Розглянуто особливості моделювання статичних систем методами інтервального аналізу експериментальних даних. Розроблено систему формальних критеріїв для оцінки якості структури інтервальних моделей. Запропоновано методи і алгоритми структурної ідентифікації інтервальних моделей статичних систем для випадків активного і пасивного експериментів. Наведено приклади застосування інтервальних методів структурної ідентифікації для моделювання статичних систем Features of static systems modeling on the basis of methods of interval analysis of experimental data are considered. The system of formal criteria is developed for the estimation of quality of the interval models structure. Methods and algorithms of the structural identification of interval models of static systems are offered for cases of active and passive experiments. Examples of application of interval methods of structural identification are considered for modeling the static systems.